1976
DOI: 10.1073/pnas.73.12.4565
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose biosynthesis in Acetobacter xylinum: visualization of the site of synthesis and direct measurement of the in vivo process.

Abstract: In vivo synthesis of cellulose by Acetobacter xylinum was monitored by darkfield light microscopy. Cellulose is synthesized in the form of a ribbon projecting from the pole of the bacterial rod. The Cellulose biosynthesis by Acetobacter xylinum has been widely investigated (1)(2)(3)(4)(5)(6). It is generally believed that the synthesis of microfibrils occurs by an extracellular process involving the sequential addition of glucose residues to the growing tips at a distance from the cell (5-7). The biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
261
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 431 publications
(271 citation statements)
references
References 21 publications
(21 reference statements)
5
261
1
Order By: Relevance
“…12,13 The microfibril cross-sections for bacterial cellulose are 10 Â 50 nm. 14 It is estimated that the lengths of all these microfibrils are at least several micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The microfibril cross-sections for bacterial cellulose are 10 Â 50 nm. 14 It is estimated that the lengths of all these microfibrils are at least several micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, it was generally believed that the synthesis of crystalline microfibrils by Acetobacter is an extracellular process. The work of Brown and co-workers (2) and Zaar (18) has now shown that cellulose is produced in close contact with the bacterial envelope. Each bacterium assembles on its surface one flat ribbon consisting of cellulose.…”
mentioning
confidence: 99%
“…The microfibrils lie side by side in a horizontal axis, thus giving rise to the fiat ribbon-like structures. Most ribbons are twisted in a very regular manner (2,18). Ribbons reaching more than 10 ~m in length project over one pole of the rod-like bacteria and taper to a point at the end distant from the cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations